Experiência inicial de auto treinamento do ator a partir dos princípios de Stanislavski - Carvalho, Eliete Alves (Universidade Federal do Tocantins, 2021)
The contributions of Constantin Stanislavski's thought and work are still applied and experienced today. This study is about the preparation and training of the actor. The choice for this research arose from the lessons of interpretation and the desire to delve into other experiences of training the actor. The interest of knowing other strategies of training like the one of the author Stanislavski and its system appeared. I propose to analyze the contributions of the initial experience of self-training from the principles of Stanislavski, where the objective is to experience the principles of the book 'The preparation of the actor'. I emphasize the need to discuss self-training and think about strategies for methodologies for beginners in the theater. This is a case study of an operational experience based on a bibliographical research. I intended with this initiative to make self-training more creative for the actor. It is understood that the principles of the author Stanislavski makes possible in the understanding of the creation of characters, to know and adapt to the historical context that the dramatic text. This monograph shows the importance of continuing to study the theorist Constantin Stanislavski because it can help to establish a strong student / actor relationship with his / her principles, helping to understand the place of creativity, body and imagination, and even understand the relation of the artist teacher with the technique of training until arriving at the process of creation.